La ricerca scientifica al tempo dei social media - Fedeli, Laura (Traiettorie inclusive - Open Access, 2017)
The book, after introducing the concept of "digital scholarship" and the interpretative nodes connected to it, retraces the issues related to the implications of the social media usage in the scientific production workflow. A conclusive reflection shifts the attention from technology as a support to the research to tecnology as an object of the research, by introducing digital ethnography and delimiting the ​​discussion area to a specific medium, the multi-user virtual worlds.